DIVERSITY OF SPECIES FISH IN THE ECOTOURISM AREA MANGROVE BEACH IN INDAH KAPUK JAKARTA - Fitrianingsih, Dessy; Febrianingrum, Sukma; Suryanda, Ade (RUMPHIUS, 2021)
This study aims to analyze the diversity of fish species found in the Mangrove Ecotourism area in Pantai Indah Kapuk. This research was conducted 2 times, namely on May 26 -June 12 2020. Fish sampling in this study used a data survey method. The results obtained were 39 fish which were classified into 8 fish species and belonged to 6 families. The goldfish species (Cyprinus carpio) belonging to the Cyprinidae family is the species with the highest number found in the Pantai Indah Kapuk Mangrove Ecotourism area. From observations made at 2 stations, 9 goldfish (Cyprinus carpio) were obtained. Apart from carp (Cyprinus carpio), the most common species found in the 2 research stations was catfish (Clarias gariepinus) with a total of 7, followed by mujaer fish (Oreochromis mossambicus) and swamp sedge fish (Trichogaster trichopterus), each of which found as many as 5 tails. Then other species have a number of individuals that vary between 3-4 tails. Based on the results of research conducted at 2 stations, the Fish Species Diversity index in the Mangrove Ecotourism Area in Pantai Indah Kapuk is in the low category with a value of 1.9.